The visibilities and invisibilities of race entangled with forensic DNA phenotyping technology - Queirós, Filipa (2019)
Forensic DNA phenotyping (FDP) technology represents a set of techniques that aim to predict physical features of criminal suspects, such as eye, skin and hair colour, and also ethnicity through the inference of biogeographic ancestry from their biological samples. In contrast to other forensic technologies, FDP is not used for identifi- cation purposes but valued for its potential intelligence value. Since features predicted by FDP relate to common traits shared by different population groups, critical voices highlight that this technology may (re)create dy- namics of collectivisation of suspect populations. Looking at the criminal justice system, this paper aims to explore the diverse understandings of FDP by professionals working in forensic laboratories and by the members of police forces, alongside the automatic exchange of genetic profiles to fight cross-border crime. Their perceptions are explored according to the per- ceived potential investigative value and potential threats of FDP. Furthermore, we discuss how racial issues are implicitly and explicitly present in these narratives. Results show that FDP may be ushering in a new assemblage of racial issues along three entangled dimensions: the differentiating power of externally visible characteristics, the comparison between genetic and eyewitness testimonies, and the collectivisation of suspicion.